Предмет: Алгебра,
автор: malikakz24
Решать уравнение
(5x+6)^2-(5x-6)^2=12
Ответы
Автор ответа:
0
(5x + 6)^2 - ( 5x - 6)^2 = 12
25x^2 + 2*5*6x + 36 - (25x^2 - 2*5*6x + .36) - 12 = 0
25x^2 + 60x + 36 - 25x^2 + 60x - 36 - 12 = 0
120x - 12 = 0 // : 12
10x - 1 = 0
10x = 1
x = 1/10 = 0, 1
25x^2 + 2*5*6x + 36 - (25x^2 - 2*5*6x + .36) - 12 = 0
25x^2 + 60x + 36 - 25x^2 + 60x - 36 - 12 = 0
120x - 12 = 0 // : 12
10x - 1 = 0
10x = 1
x = 1/10 = 0, 1
Автор ответа:
0
Это умножение
Автор ответа:
0
по формуле квадрата суммы и разности
25x^2+60x+36-(25x^2-60x+36)=12
раскроем скапку
25x^2-25x^2+60x+60x+36-36=12
приведем подобные
120x=12
поделим на 12
10x=1
перенесем 10 в правую часть путем деления
x=0.1
25x^2+60x+36-(25x^2-60x+36)=12
раскроем скапку
25x^2-25x^2+60x+60x+36-36=12
приведем подобные
120x=12
поделим на 12
10x=1
перенесем 10 в правую часть путем деления
x=0.1
Похожие вопросы
Предмет: Алгебра,
автор: rofawin828
Предмет: Қазақ тiлi,
автор: anel20070612
Предмет: Математика,
автор: madinamahmud84
Предмет: Литература,
автор: Leravolonina